Religion as a Tool of Political Manipulation in Nigeria - Anifowose, Oluwaseun Adeola (Àgídìgbo: ABUAD Journal of the Humanities, 2017)
The Nigerian political system exemplifies manipulation of all sorts and in various forms with religion serving as one of the structuresthrough which this manipulation takes place. This paper intends to address the role of religion in serving as a means through which members of the political class manipulates the country’s polity and undermine the nation’s political framework. While some have argued that since religion is an integral part of the society, it has a role to play to deterring the political destiny of a nation, others on the hand vehemently oppose this claim assertion claiming that religion has been hijacked by political elites and has become an instrument to further their political plans, perpetuate political ills, manipulate political decisions of Nigerians and ultimately enslave the people. This paper argues that there is an urgent need for de-politization of religion and separation of politics from religion if Nigerians are to achieve freedom from political manipulation and enslavement by the Nigerian politicians.